Best Management Practices in urban park management by the Kuala Lumpur Federal Authority, Malaysia - Abdul Aziz, Nor Azah (2023)
Park visitation is a popular recreational activity among urban residents. These attractions are related to park’s products such as park’s facilities, services and programs that enable visitors to enjoy their visit and have memorable experience. This research investigates urban parks management issues. Therefore, the purposes of this research are to identify and understand the management issues that occurs in mostly urban parks as well as to determine the proper management that will associated with best practices to be adopt in order to justify a safe and first-class environment in an urban park. The study’s aim is to identify and analyse the Strategic Framework in Integrating “Best Management Practices” (BMP) for urban park in Kuala Lumpur Malaysia. As stated in National Landscape Policy action plans under Thrust 3 Strategy 3.2 “Encourage Manageable and Sustainable Landscape Development Programs in Order to Achieve Beautiful Garden Nation”. A good management in maintaining the urban parks is to provide a holistic path towards a better-quality living environment. It is an important initiative towards an effective quality of life by providing safe, healthy and clean landscape. Urban park is a valuable asset. Its preservation and maintenance contribute directly to the environment and socioeconomic development. The strategic approach and method for this research is by recognizing the existing urban park management principles that are available. This research used a qualitative method approached. The data collection will be collected through interview with selected respondents such as academician, landscape architects, botanists, park managers, expertise and local authority. In executing the interview process, the researcher had chosen the semi-structured open-ended questions, in-depth interview method and conducted by site observation to evaluate the BMP performance and validate the written documents. The findings from this study will enabled park management to identify the BMP that represent the overall urban park management towards sustainability in Kuala Lumpur. The result of the study show that application of BMP is the key to improve the management efficiency and practicality of urban park. At the end of the research, several recommendations of BMP for urban parks in Kuala Lumpur have been put forward as mitigation measures in order to sustain, to plan strategies and way forward towards first-class landscape management.